2018
DOI: 10.1007/s10735-018-9760-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-484/MAP2/c-Myc-positive regulatory loop in glioma promotes tumor-initiating properties through ERK1/2 signaling

Abstract: Glioma is the most common intracranial malignant tumor. Cancer stem cells (CSCs) are resistant to chemotherapy and radiotherapy, and are closely related to cancer metastasis and recurrence. In this study, we aimed to explore the effect of miR-484 on glioma stemness and the underlying mechanism involved. miR-484 enhanced glioma tumor-initiating properties in vitro and in vivo. Moreover, miR-484 was shown to directly target MAP2, resulting in activation of ERK1/2 signaling and promotion of stemness in glioma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…Some researchers argue that MAP2 plays a dual role in the progression of cancer, which was studied in non-glioma tumors (Song et al, 2016). However, some authors assert that MAP2 may even be a positive marker of glioma, as shown in (Yi et al, 2018). However, in our work, we do not see a positive prognostic value of increased MAP2 expression for a patient.…”
Section: Fig 4 Normalized Expression Of Target Genes In Human Gliobcontrasting
confidence: 61%
“…Some researchers argue that MAP2 plays a dual role in the progression of cancer, which was studied in non-glioma tumors (Song et al, 2016). However, some authors assert that MAP2 may even be a positive marker of glioma, as shown in (Yi et al, 2018). However, in our work, we do not see a positive prognostic value of increased MAP2 expression for a patient.…”
Section: Fig 4 Normalized Expression Of Target Genes In Human Gliobcontrasting
confidence: 61%
“…However, there are also some limitations in our study. Previous studies have demonstrated that miR-484 can reduce the expression of a series of oncogenes, such as ZEB1, SMAD2, etc., inhibit the epithelial-mesenchymal transition (EMT) of tumor cells, or regulate the extracellular signal-regulated kinase 1/2 signaling [16,34,38]. The precise molecular mechanisms underlying the role of miR-484 should be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that miR-484 directly targets MAP2, which causes downstream ERK1/2 signal transduction to activate cancer stem cell characteristics and promote glioma tumorigenesis [27]. miR-484 can also inhibit Apf-1 expression to promote NSCLC proliferation and inhibit apoptosis in tumor cells to promote NSCLC development [28].…”
Section: Discussionmentioning
confidence: 99%